Study of Bee Gum and Beehive modes hiving - CHASENGSONG , Kisong; SISOUPHANH, Somemay (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This study aims to investigate two methods of bee hives, ancient wooden beehives and beehives (hive boxes) modes including income investigation of honey during the February to May 2019. The research was conducted in four villages of Phoukout district of Xieng Khouang Province by randomly 50 families of beekeepers as sample. The results showed that beekeepers prepare the hive by select and cut the tree with bee colony to make ancient wooden beehives, while the beehives used wood to make a box and spirit of the beehives from one to others. On average, beekeepers contacted agricultural extension officers to help beehives. Fifty-five farmers reported that beehive (boxes) mode is easier ways to hive than ancient wooden bee hives such as management, honey collection, spirit of beehive to other hives. For the honey production, the results from two modes indicated that honey production from ancient wooden beehive mode share the same output of honey with beehive at 3.69 liters/hive and 4.83 liters/hive respectively. More beekeepers harvest honey only once a year, ancient wooden bee hive mode with production honey 21.63 liters/year while beehive modes with productions honey 25.41liters/year. However, income of honey was higher in beehive mode than in the ancient wooden beehive mode as 1,090,000 kips/family and 839,513 kips/family, respectively. Beekeepers are sold honey bee in two categories: raw honey and honey with dehydrate moisture; raw honey is 35,000 kips/liters and dehydrate moisture honey is 50,000 kips/liters. The beeswax remaining in hive of two modes were not been used to make other products. Therefore, In order to encourage beekeepers in further, beekeepers should attend on hive calendar, bee management and honey processing for good products in future.